Reliability evaluation of a 0.25 μm SiGe technology for space applications. (September 2019) - Robin, C.; Rochette, S.; Desgrez, S.; Muraro, J.L.; Langrez, D.; Roux, J.L.; Krstic, M.
Abstract: This article presents a reliability evaluation of the SiGe SGB25 technology from the European foundry IHP. We propose in this paper a methodology allowing to take into account reliability space requirements. For that, specific test vehicles have been designed and dedicated test sequences have been defined. The final goal is to define a MMIC (Monolithic Microwave Integrated Circuit) safe operating area in terms of static and dynamic electrical constraints. Emphasis will be given to the influence of the degradation modes on noise parameters.